Ground-Water-Quality Data for Selected Wells in the Beaver Creek Watershed, West Tennessee - Williams, Shannon D. (1996)
In 1993 the U.S. Geological Survey, in cooperation with the Tennessee Department of Environment and Conservation, began an investigation of the quality of ground water in the Beaver Creek watershed in West Tennessee. A total of 408 water samples were collected from 91 wells during 5 sampling periods in 1994. Water samples were analyzed for selected water-quality properties, fecal coliform and streptococci bacteria, nutrients, and selected inorganic constituents. Selected well-construction data and information on potential sources of contamination near the sampled wells were also collected. Nitrate concentrations (measured as NO+ ranged from a detection limit of 0.1 to 9 1 milligrams per liter (mg/L). Nitrate concentrations exceeding 13 mg/L were detected in 7 1 of the samples collected. Nitrate concentrations in samples from three wells exceeded the Tennessee Department of Environment and Conservation primary drinking water standard of 44 mg/L for nitrate (measured as NO$. Nitrite (measured as NOT), ammonium (measured as NH,), and orthophosphate (measured as P04) concentrations were generally less than 0.1 mg/L (detection limit). Fecal coliform bacteria were detected in 33 of the 408 samples collected. Samples from 21 of the 91 wells contained fecal coliform bacteria during 1 or more of the 5 sampling periods. Fecal streptococci bacteria were detected in 123 of the 408 samples collected. Samples from 59 of the 91 wells contained fecal streptococci bacteria during 1 or more of the 5 sampling periods. Prepared in cooperation with the Tennessee Dept. of Environment and Conservation.